Comparison of Pediatric Severe Sepsis Managed in U.S. and European ICUs - Giuliano, J.; Markovitz, B.; Brierley, J.; Levin, R.; Williams, G.; Lum, L.; Dorofaeff, T.; Cruces, P.; Bush, J.; Keele, L.; Nadkarni, V.; Thomas, N.; et al. (Lippincott Williams & Wilkins, 2016)
Copyright © 2016 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.Objectives: Pediatric severe sepsis remains a significant global health problem without new therapies despite many multicenter clinical trials. We compared children managed with severe sepsis in European and U.S. PICUs to identify geographic variation, which may improve the design of future international studies. Design: We conducted a secondary analysis of the Sepsis PRevalence, OUtcomes, and Therapies study. Data about PICU characteristics, patient demographics, therapies, and outcomes were compared. Multivariable regression models were used to determine adjusted differences in morbidity and mortality. Setting: European and U.S. PICUs. Patients: Children with severe sepsis managed in European and U.S. PICUs enrolled in the Sepsis PRevalence, OUtcomes, and Therapies study. Interventions: None. Measurements and Main Results: European PICUs had fewer beds (median, 11 vs 24; p < 0.001). European patients were younger (median, 1 vs 6 yr; p < 0.001), had higher severity of illness (median Pediatric Index of Mortality-3, 5.0 vs 3.8; p = 0.02), and were more often admitted from the ward (37% vs 24%). Invasive mechanical ventilation, central venous access, and vasoactive infusions were used more frequently in European patients (85% vs 68%, p = 0.002; 91% vs 82%, p = 0.05; and 71% vs 50%; p < 0.001, respectively). Raw morbidity and mortality outcomes were worse for European compared with U.S. patients, but after adjusting for patient characteristics, there were no significant differences in mortality, multiple organ dysfunction, disability at discharge, length of stay, or ventilator/vasoactive-free days. Conclusions: Children with severe sepsis admitted to European PICUs have higher severity of illness, are more likely to be admitted from hospital wards, and receive more intensive care therapies than in the United States. The lack of significant differences in morbidity and mortality after adjusting for patient characteristics suggests that the approach to care between regions, perhaps related to PICU bed availability, needs to be considered in the design of future international clinical trials in pediatric severe sepsis.